The Influence of Individual Attributes On Inter-Ethnic Tolerance among Early Youth In Selangor - Idris, Fazilah (2008)
The development, survival, and continuity of Malaysia lie on the shoulders of young Malaysians. As such, youth should demonstrate a higher level of understanding and greater tolerance in order to maintain peace and harmony. In line with that, the objective of this study is to determine the influence of individual attributes on inter-ethnic tolerance among early youth in Selangor. And, it focused on the influence of cognitive readiness, personality traits and religious personality on attitude, which would in turn, influence how an individual behaved in a multi-cultural situation. The Theory of Planned Behavior (TPB) framework (Fishbein and Ajzen, 1991) was used to model the relationships among the three selected independent variables that contributed toward inter-ethnic tolerance behavior. As many as 563 secondary school students in Selangor, representing early youth, participated in this study. This study adopted the exploratory design and survey data collection method. Instruments used were the Malay translated NEO PI-R Personality Inventory (NEO PI-R), a self- designed questionnaire on the Inter-ethnic Tolerant Behavior (IETB) and Universal Religious Personality Inventory (URPI). The study found that more than half of the youth possessed high level of cognitive readiness. For Malay and Indian youth, the majority have high level of cognitive readiness, while more female youth tend to have high cognitive readiness compared to male. In terms of attitude, majority of the respondents were found to have high level of positive attitude regarding inter-ethnic relations. Gender, religion and the level of religious practice significantly contribute to youth attitude towards Inter-ethnic Tolerant Behavior (IETB). In terms of the level of IETB, the majority of the Malay and Chinese early youth displayed a moderate level; however, the majority of the Indian youth have a high level of IETB. The findings indicated that cognitive readiness, all personality traits, except for the domain of Neuroticism, and all three types of religious personality (pro-social, ritual and anti-social) significantly influenced the youth’s willingness to accept issues regarding inter-ethnic relations. Specifically, pro-social and ritual behavior influenced youth attitude positively, while the influence of anti-social behavior on attitude was negative. The study improved the proposed model which was based on Theory of Planned behavior (TBP) and confirmed the impact of cognitive readiness, personality traits and religious personality on youth attitude, and the impact of the youth attitude on their behavior on inter-ethnic issues. The study also found that cognitive readiness is the most influential factor to IETB, and that both cognitive readiness and religious personality influenced inter-ethnic tolerant behavior directly and indirectly as well through attitude. Inter-ethnic tolerant behavior (IETB) among students may be improved through enhancing cognitive readiness, pro-social behavior, attitude and openness of the individuals.